Chronic enteropathy in dogs affects the quality of life in both dogs and their owners—are veterinarians proficient in handling the caregiver burden? - Lyngby, Janne Graarup-Hansen; Nielsen, Lise Nikolic; Ankerkilde, Stine; Bentzen, Amanda Wissendorf; Bjørnvad, Charlotte; Lund, Thomas Bøker; Sandøe, Peter (Frontiers in Veterinary Science, 2025)
IntroductionChronic disease is generally known to affect dogs’ quality of life (QoL) as well as being associated with increased strain on their owners. Gastrointestinal (GI) disease is a common problem in companion animal practice, yet little is known about the QoL of dogs with chronic enteropathy (CE) and how their owners and veterinarians assess it.MethodsThe aim of this study was to explore: (i) how dog owners and veterinarians observed and evaluated QoL for dogs with chronic GI disease, (ii) how having a dog with CE affected the owner’s QoL, and (iii) characteristics of the communication and relationship between the dog owner and veterinarian. Twenty owners of dogs with CE and 20 companion animal veterinarians were included in this qualitative, interview-based, exploratory study.ResultsOwners evaluated QoL based on their dog’s apparent emotional state, the presence of clinical signs, or restrictions in their daily life. In their assessments, veterinarians looked at the presence or absence of normal behavior, but also at disease severity and the emotional state of the dog. The majority of owners experienced many concerns and burdens that impacted their own QoL, including daily logistical challenges, implementing therapeutic regimens such as diet restriction, administering multiple daily medications, and the strain of nursing responsibilities on the owner-dog relationship. Dog owners generally felt that communication with their veterinarians was good, while veterinarians found the communication laborious and time-consuming.DiscussionIn general, owners and veterinarians were aligned in their QoL assessments, and the majority of veterinarians relied heavily on the owners’ input and observations. However, assessments were not done in a standardized fashion among either group. Logistical challenges of having a dog with a chronic GI disease often lead to lifestyle changes for the owners, including altering working hours and cancelling holidays or other social arrangements. Having a dog with CE therefore affected the owners’ QoL even when the dogs were clinically stable. Providing owners with written material about the condition in addition to medical and feeding regimen instructions may help the owner, improve compliance, and decrease the non-billable hours the veterinarian must spend communicating with the owner about their dog’s CE.